Resilience in Community: A Social Ecological Development Model for Young Adult Sexual Minority Women. Issue 1 (9th January 2015) - Zimmerman, Lindsey; Darnell, Doyanne A.; Rhew, Isaac C.; Lee, Christine M.; Kaysen, Debra
Abstract: Family support and rejection are associated with health outcomes among sexual minority women (SMW). We examined a social ecological development model among young adult SMW, testing whether identity risk factors or outness to family interacted with family rejection to predict community connectedness and collective self‐esteem. Lesbian and bisexual women (N = 843; 57 % bisexual) between the ages of 18–25 (M = 21.4; SD = 2.1) completed baseline and 12‐month online surveys. The sample identified as White (54.2 %), multiple racial backgrounds (16.6 %), African American (9.6 %) and Asian/Asian American (3.1 %); 10.2 % endorsed a Hispanic/Latina ethnicity. Rejection ranged from 18 to 41 % across family relationships. Longitudinal regression indicated that when outness to family increased, SMW in highly rejecting families demonstrated resilience by finding connections and esteem in sexual minority communities to a greater extent than did non‐rejected peers. But, when stigma concerns, concealment motivation, and other identity risk factors increased over the year, high family rejection did not impact community connectedness and SMW reported lower collective self‐esteem. Racial minority SMW reported lower community connectedness, but not lower collective self‐esteem. Families likely buffer or exacerbate societal risks for ill health. Findings highlight the protective role of LGBTQ communities and normative resilience among SMW and their families.